ПРОБЛЕМА БЕСКОНЕЧНОСТИ ЯЗЫКА (ТЕКСТА) В ПОСТСТРУКТУРАЛИСТСКОМ ПОДХОДЕ (Philological Studies, 2019)
The author speaks about the relation of language (text) and infinity in poststructuralist’s researches.